2021
DOI: 10.1002/jso.26457
|View full text |Cite
|
Sign up to set email alerts
|

Curettage and cryosurgery for enchondroma and atypical cartilaginous tumors of the long bones: Oncological results of a large series

Abstract: Background and Objectives: Intralesional surgical treatment is the preferred therapy for atypical cartilaginous tumors (ACTs) of the long bones in many institutions. However, the literature is still controversial regarding intralesional treatment versus wide resection. Due to the relative rarity of these tumors, studies reporting on the results of intralesional treatment are often small sample studies. Methods: We retrospectively analyzed the oncological results of 55 enchondromas, 119 ACTs, and 5 chondrosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…In the authors' patients, the evolution in subsequent radiographic follow-up (including the luck of having a previous radiograph in the first case) and the absence of symptoms before the fracture were considered sufficient to warrant the diagnosis of benignity and endorse the decision of conservative management over surgery with further morbidity. 4,11,19,20 CONCLUSION These cases illustrate this paper's conclusion: a pathological fracture in a long bone revealing a chondroid tumor of uncertain aggressiveness should be managed cautiously. In the absence of endosteal scalloping and a healed fracture, after informed consent, it would be reasonable to consider long-term (5+ years) observation for changes concerning for an active lesion.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In the authors' patients, the evolution in subsequent radiographic follow-up (including the luck of having a previous radiograph in the first case) and the absence of symptoms before the fracture were considered sufficient to warrant the diagnosis of benignity and endorse the decision of conservative management over surgery with further morbidity. 4,11,19,20 CONCLUSION These cases illustrate this paper's conclusion: a pathological fracture in a long bone revealing a chondroid tumor of uncertain aggressiveness should be managed cautiously. In the absence of endosteal scalloping and a healed fracture, after informed consent, it would be reasonable to consider long-term (5+ years) observation for changes concerning for an active lesion.…”
mentioning
confidence: 74%
“…The clinical and imaging data before the fracture and subsequent behavior are crucial in the diagnosis and management. In the authors’ patients, the evolution in subsequent radiographic follow-up (including the luck of having a previous radiograph in the first case) and the absence of symptoms before the fracture were considered sufficient to warrant the diagnosis of benignity and endorse the decision of conservative management over surgery with further morbidity 4,11,19,20…”
Section: Discussionmentioning
confidence: 98%
“…Eine kostengünstigere und weniger toxische Alternative stellt Wasserstoffperoxid dar, dessen Effektivität bei Riesenzelltumoren des Knochens bestätigt wurde [25]. Auch flüssiger Stickstoff, welcher mindestens 2-mal hintereinander in die Tumorhöhle instilliert werden muss, um gute zytotoxische Effekte zu erzielen, kann als Adjuvans zur Anwendung kommen [7,34].…”
Section: Adjuvanzienunclassified
“…The different diagnostic imaging features of ACTs, which mainly occur in the long bones more proximally (especially within the femur), and enchondromas, which most commonly appear in the proximal humerus or more distally in the long bones, have been discussed previously [ 9 , 16 ]. Murphey et al evaluated differentiating criteria for enchondromas and chondrosarcomas (including former grade 1) and showed that cortical destruction, soft tissue mass, periosteal reaction and endosteal scalloping (>2/3 of cortical thickness) strongly suggested the diagnosis of chondrosarcoma.…”
Section: Introductionmentioning
confidence: 99%